Assessing small airway impairment in mild-to-moderate smoking asthmatic patients. Issue 4 (12th February 2016) - Contoli, Marco; Bellini, Federico; Morandi, Luca; Forini, Giacomo; Bianchi, Stefano; Gnesini, Giulia; Marku, Brunilda; Rabe, Klaus F.; Papi, Alberto
Asthma is characterised by airway inflammation throughout the bronchial tree, including the small airways. In asthma, small airway alterations are associated with poor clinical outcomes [1]. Cigarette smoke is known to induce peripheral airway abnormalities, asthmatic smokers exhibit a more rapid lung function decline, experience more frequent exacerbations and are more likely to be uncontrolled, even when the disease is managed as recommended [2]. The mechanisms accounting for poor responses to treatment in smoking asthmatic patients are currently unclear, although low accessibility to inhaled medications in the peripheral airways is considered a limiting factor for the efficacy of such treatments [3]. Cigarette smoking enhances small airways impairment in asthmatic patients http://ow.ly/WWUky